Strain and temperature sensitivities of an elliptical hollow-core photonic bandgap fiber based on Sagnac interferometer - Kim, Gilhwan; Cho, Taiyong; Hwang, Kyujin; Lee, Kwanil; Lee, Kyung S.; Han, Young-Geun; Lee, Sang Bae (OPTICAL SOC AMER, 2009)
We fabricated an elliptical hollow-core photonic bandgap fiber (EC-PBGF) by controlling lateral tension in the hollow core region during the fiber drawing process. The absolute value of group modal birefringence becomes relatively high near the bandgap boundaries. We also experimentally measured the strain and temperature sensitivities of the fabricated EC-PBGF-based Sagnac loop interferometer. The strain and temperature sensitivities were very much dependent upon the wavelength. Moreover this PBGF-based interferometer can be a good sensor of physical parameters such as strain and temperature. (C) 2009 Optical Society of America
Keywords: POLARIZATION PROPERTIES; CRYSTAL FIBERS; SURFACE-MODES; BIREFRINGENCE; PRESSURE